Penatalaksanaan Fisioterapi pada Kondisi Cerebral Palsy Spastic Athetoid Quadriplegi Tipe Ekstensi et causa Hemiatrofi Cerebri Sinistra dengan Metode Neuro Development Treatment (NDT) di Klinik Griya Fisio Bunda Novy Yogyakarta - Anugraheni, Rana, Edy Waspada, S. Fis., M. Kes, Umi Budi Rahayu, S.Fis, M.Kes, Totok Budi Santoso , S.Fis , MPH (2017)
NEURO DEVELOPMENT MANAGEMENT TREATMENT AT CEREBRAL PALSY SPASTIC ATHETOID QUADRIPLEGI IN GRIYA PHYSIO BUNDA NOVY YOGYAKARTA (Rana Anugraheni, J100140012, 2017, 49 pages) ABSTRACT Background: Cerebral Palsy is disorder posture and movement because of immature brain damage that occurs during pregnancy and chilhood. While, Cerebral Palsy Spastic Athetoid Quadriplegi is a disorder posture and movement causes by damage to the central nervous system of the brain that is non-progressive characterized by spasticity and weakness of the four limbs. Physiotherapy modalities used in the metod of Neuro Development Treatment (NDT). Purpose: To investigate the management of Neuro Development Treatment at condition of Cerebral Palsy Spastic Athetoid Quadriplegi to control spasticity, improve functional ability, and increase muscle strength. Result: After therapy 6 times result (1) spasticity that persistent from T1 to T6 measure by Asworth scale, the shoulder, elbow, knee, and ankle obtained a value to 1, wrist and hip obtained a value to 0, (2) functional abilty as measured by GMFM from T1 to T6 fixed the value obtained persist at 12,25%, (3) unchanged muscle strength from T1 to T6 that measure by X0TR, the shoulder, elbow wrist, and knee obtained a value to X, hip obtained a value to T, and ankle obtained a value to R. Conclusion: Neuro Development Treatment (NDT) management at Cerebral Palsy Spastic Athetoid Quadriplegi to controled of spasticity, improve functional ability, and increase muscle strength has not changed significantly. Keywords: Cerebral Palsy, Neuro Development Treatment (NDT), Asworth scale, Gross Motor Functional Measure (GMFM).